Suppressor of cytokine signalling 2 (SOCS-2) expression in breast carcinoma. Issue 10 (27th September 2005) - Farabegoli, F; Ceccarelli, C; Santini, D; Taffurelli, M
Abstract : Aims: To investigate SOCS-2 (suppressor of cytokine signalling 2) protein expression in breast carcinoma samples in relation to biopathological parameters and survival. Methods: A polyclonal antibody against SOCS-2 was used to study 50 archival breast carcinoma samples, collected from 1993 to 1995. The presence of SOCS-2 protein was investigated in relation to clinical and biological parameters used in breast cancer pathology. Fluorescence in situ hybridisation (FISH) was used to study whether SOCS-2 expression was related to SOCS-2 gene copy number. Results: SOCS-2 protein was expressed in 34 of 50 breast carcinoma samples and was positively associated with low grade, low nuclear grade, and p27 protein. SOCS-2 expression was inversely related to Ki-67, cyclin A, retinoblastoma protein (pRb), and the epidermal growth factor receptor (EGFR). No relation with overall survival was demonstrated. SOCS-2 amplification was found in three samples. No relation between the number of FISH signals and SOCS-2 expression was found. Conclusions: The significant correlation seen between SOCS-2 expression, grade, nuclear grade, p27, Ki-67, cyclin A, pRb, and EGFR labelling strongly supports the hypothesis that SOCS-2 loss might be related to cell proliferation and tumour growth in breast carcinoma. Gene copy number changes did not seem to play a role in SOCS-2 regulation and expression; other mechanisms might be involved and deserve further study.